KEKUATAN NILAI “PANCASILA” SEBAGAI IDEOLOGI NEGARA UNTUK KEBERLANGSUNGAN HIDUP BANGSA - Anggian Cassilas; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
The formulation of Pancasila is stated in the Preamble to the 1945 Constitution. Pancasila has officially become the basis of the state, the ideology of the state, and has become a source of law in legislation since August 18, 1945. As a state ideology, the values of the Pancasila precepts must be instilled in the nation from an early age. This is important to preserve culture and maintain the integrity of the Republic of Indonesia from threats to state ideology. Education about Pancasila is one example and a way to instill a person who is moral and broad-minded in the life of the nation and the state. With the erosion of Pancasila values in people's lives, it triggers the threat of losing the nation's character and other forms of threats such as threats from within the country and from abroad which of course can harm the community in the nation and state. Threats can be in the form of physical or non-physical threats that can occur at any time and can attack anyone. Therefore, it is important for the Indonesian people to explore the nation's ideology, namely Pancasila and make it a way of life in the nation to be able to advance the general welfare as one of the sounds of the state's goals stated in the fourth paragraph of the Preamble to the 1945 Constitution.